Evaluating the impacts of osmotic and oxidative stress on common carp (Cyprinus carpio, L.) sperm caused by cryopreservation techniques - Li, Ping; Li, Zhi-Hua; Dzyuba, Boris; Hulak, Martin; Rodina, Marek; Linhart, Otomar (Biology of reproduction, 2010)
Cryopreservation causes osmotic changes and oxidative damage that have sublethal and lethal effects on spermatozoa. We examined these osmotic and oxidative effects on common carp spermatozoa motility; membrane integrity; levels of thiobarbituric-acid-reactive substance (TBARS) and carbonyl groups (CP); and the activity of superoxide dismutase (SOD), glutathione reductase, and glutathione peroxidase (GPx). Sperm was diluted in dimethyl sulfoxide (DMSO) and ethylene glycol-based extenders, followed by equilibration, freezing, and thawing. Equilibration in DMSO extender resulted in a significant reduction of spermatozoa motility, but motility was induced in those spermatozoa following dilution with saline buffer, which usually inhibits undiluted spermatozoa motility. Spermatozoa velocity and membrane integrity decreased with both extenders following freezing and thawing. No significant difference in levels of TBARS or CP, or in SOD activity, was seen in samples equilibrated with either extender. The freeze/thaw process induced significantly higher levels of TBARS, CP, and GPx activity, but did not affect the level of SOD. Glutathione reductase activity was inhibited in samples exposed to DMSO extender. Ethylene glycol should be considered a preferred cryoprotective agent for common carp spermatozoa to reduce osmotic and oxidative stress during cryopreservation.
Keywords: Animals; Cryopreservation; Superoxide Dismutase; Thiobarbituric Acid Reactive Substances; Ethylene Glycol; oxidační stres; glutathionperoxidasa; Dimethyl Sulfoxide; spermie; superoxiddismutasa; ethylenglykol; osmotický tlak; Protein Carbonylation; Spermatozoa; kapři; Oxidative Stress; Cryoprotective Agents; videomikroskopie; vodní hospodářství; Osmotic Pressure; motilita spermií; Aquaculture; kryoprezervace; Glutathione Peroxidase; rybí proteiny; dimethylsulfoxid; Male; karbonylace proteinů; Fish Proteins; Carps; Sperm Motility; zvířata; mužské pohlaví; kryoprotektivní látky; buněčná membrána; Glutathione Reductase; glutathionreduktasa; látky reagující s kyselinou thiobarbiturovou; Cell Membrane; Microscopy, Video